CT imaging for evaluation of calcium crystal deposition in the knee: initial experience from the Multicenter Osteoarthritis (MOST) study. Issue 2 (February 2015) - Misra, D.; Guermazi, A.; Sieren, J.P.; Lynch, J.; Torner, J.; Neogi, T.; Felson, D.T.
Summary: Objective: Role of intra-articular calcium crystals in osteoarthritis (OA) is unclear. Imaging modalities used to date for its evaluation have limitations in their ability to fully characterize intra-articular crystal deposition. Since Computed Tomography (CT) imaging provides excellent visualization of bones and calcified tissue, in this pilot project we evaluated the utility of CT scan in describing intra-articular calcium crystal deposition in the knees. Method: We included 12 subjects with and four subjects without radiographic chondrocalcinosis in the most recent visit from the Multicenter Osteoarthritis (MOST) study, which is a longitudinal cohort of community-dwelling older adults with or at risk for knee OA. All subjects underwent CT scans of bilateral knees. Each knee was divided into 25 subregions and each subregion was read for presence of calcium crystals by a musculoskeletal radiologist. To assess reliability, readings were repeated 4 weeks later. Results: CT images permitted visualization of 25 subregions with calcification within and around the tibio-femoral and patello-femoral joints in all 24 knees with radiographic chondrocalcinosis. Intra-articular calcification was seen universally including meniscal cartilage (most common site involved in 21/24 knees), hyaline cartilage, cruciate ligaments, medial collateral ligament and joint capsule. Readings showed good agreement for specific tissues involved with calcium deposition (kappa: 0.70, 95% CI 0.62–0.80). Conclusion: We found CT scan to be a useful and reliable tool for describing calcium crystal deposition in the knee and therefore potentially for studying role of calcium crystals in OA. We also confirmed that "chondrocalcinosis" is a misnomer because calcification is present ubiquitously.